2017
DOI: 10.1128/aem.02833-16
|View full text |Cite
|
Sign up to set email alerts
|

Sybr Green- and TaqMan-Based Quantitative PCR Approaches Allow Assessment of the Abundance and Relative Distribution of Frankia Clusters in Soils

Abstract: The nodule-forming actinobacterial genus Frankia can generally be divided into 4 taxonomic clusters, with clusters 1, 2, and 3 representing nitrogen-fixing strains of different host infection groups and cluster 4 representing atypical, generally non-nitrogen-fixing strains. Recently, quantitative PCR (qPCR)-based quantification methods have been developed for frankiae of clusters 1 and 3; however, similar approaches for clusters 2 and 4 were missing. We amended a database of partial 23S rRNA gene sequences of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…The diversity of Frankia populations, however, was relatively low, with frankiae of clusters 1b, 1e, and 3 present in nonvegetated controls, and cluster 1e and 3 frankiae generally were present in vegetated microcosms only. Previous studies reported on the low diversity of Frankia populations in different soil environments, e.g., the presence of cluster 1b only in wet or even water-logged soils in natural stands of A. glutinosa (23), clusters 1b and 3 in forest soils with A. glutinosa or nonhost plants, including Betula nigra (21,24), clusters 1a, 1b, and 3 in forest soils with A. glutinosa (21), clusters 1a and 3 in microcosms with A. glutinosa or C. equisetifolia (30), or clusters 1b, 2, 3, and 4 in prairie soils with Ceanothus species as potential host plants (24). These studies suggest soil-specific environmental effects on Frankia populations in soils, with frankiae of clusters 1b and 3 being quite ubiquitous and independent of the presence of host plant species.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The diversity of Frankia populations, however, was relatively low, with frankiae of clusters 1b, 1e, and 3 present in nonvegetated controls, and cluster 1e and 3 frankiae generally were present in vegetated microcosms only. Previous studies reported on the low diversity of Frankia populations in different soil environments, e.g., the presence of cluster 1b only in wet or even water-logged soils in natural stands of A. glutinosa (23), clusters 1b and 3 in forest soils with A. glutinosa or nonhost plants, including Betula nigra (21,24), clusters 1a, 1b, and 3 in forest soils with A. glutinosa (21), clusters 1a and 3 in microcosms with A. glutinosa or C. equisetifolia (30), or clusters 1b, 2, 3, and 4 in prairie soils with Ceanothus species as potential host plants (24). These studies suggest soil-specific environmental effects on Frankia populations in soils, with frankiae of clusters 1b and 3 being quite ubiquitous and independent of the presence of host plant species.…”
Section: Discussionmentioning
confidence: 98%
“…A single nodule was found on C. equisetifolia, with a Frankia population representing cluster 1e. Casuarina species usually produce nodules with Frankia populations of cluster 1c (24), meant to represent a group of highly specialized frankiae that depend on cointroduction with their exotic host plant species outside their native range (28,29). Consequently, Casuarina-infective Frankia populations were not expected to form nodules in soils that have never supported Casuarina spp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations